Post fire cambial activity of two evergreen sclerophyllous species in Greece. - Psaras, G.K.; Christodoulakis, N.S.; Arianoutsou-Faraggitaki, M. (Flora, Jena, 1984)
Cambial activity of post fire resprouted stems of Quercus coccifera and Olea europaea ssp. oleaster is demonstrated.-from Authors
Keywords: Olea europaea oleaster; Quercus coccifera